Dedifferentiated Liposarcoma Arising in an Esophageal Polyp: A Case Report. (14th August 2012) - Torres-Mora, Jorge; Moyer, Ann; Topazian, Mark; Alexander, Jeffrey; Wu, Tsung-Teh; Seys, Amber; Fritchie, Karen
Abstract : Liposarcoma is one of the most common sarcomas in adults, but only rarely presents as an esophageal primary. There have been several reports of well-differentiated liposarcoma (WDL) arising in the esophagus, but we present a case of dedifferentiated liposarcoma (DL) presenting as a large esophageal polyp. We believe this is the first reported case of DL of the esophagus with morphologic evidence of both well-differentiated and dedifferentiated components. The diagnosis was confirmed by demonstration of CPM gene amplification by fluorescence in situ hybridization (FISH).